Programa de capacitación para mejorar el desempeño laboral del personal administrativo de transportes Rodrigo Carranza S.A.C - Trujillo: 2016 - Miranda Chuquimango, Lenny Marisol (2016)
This research aims to determine the effect of training on job performance, for which the following question arises: How a training program improves job performance of the administrative staff of Transport Rodrigo Carranza S.A.C city of Trujillo? Determining the following hypothesis: The training program significantly enhances job performance of the administrative staff of Transport Rodrigo Carranza city of Trujillo. Collector was designed as a survey instrument with thirty-one items, applied to administrative staff and the results were expressed in tables and figures. It was obtained the following conclusion: the implementation of the training program helps improve the job performance of the administrative staff of Transport Rodrigo Carranza S.A.C.